2012
DOI: 10.3390/mi3020509
|View full text |Cite
|
Sign up to set email alerts
|

High-Q MEMS Resonators for Laser Beam Scanning Displays

Abstract: This paper reports on design, fabrication and characterization of high-Q MEMS resonators to be used in optical applications like laser displays and LIDAR range sensors. Stacked vertical comb drives for electrostatic actuation of single-axis scanners and biaxial MEMS mirrors were realized in a dual layer polysilicon SOI process. High Q-factors up to 145,000 have been achieved applying wafer level vacuum packaging technology including deposition of titanium thin film getters. The effective reduction of gas dampi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
79
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(79 citation statements)
references
References 18 publications
(13 reference statements)
0
79
0
Order By: Relevance
“…Contrary to the DLP technology in which majority of the tasks for image production are realized optically, electronic design plays a more important role for scanning-type projectors. As demonstrated in prior studies, micro-scanning mirrors may be driven by electrostatic [5][6][7][8][9][10][11][12][13][14], electromagnetic [15][16][17][18] or piezoelectric [19][20][21][22][23] mechanisms. Each approach has its own advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Contrary to the DLP technology in which majority of the tasks for image production are realized optically, electronic design plays a more important role for scanning-type projectors. As demonstrated in prior studies, micro-scanning mirrors may be driven by electrostatic [5][6][7][8][9][10][11][12][13][14], electromagnetic [15][16][17][18] or piezoelectric [19][20][21][22][23] mechanisms. Each approach has its own advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 96%
“…Few studies have demonstrated micro-scanning mirrors with on-chip capacitive [12][13], piezoresistive [14] and piezoelectric [21] sensing capabilities. Drabe et al [14] reported a bi-axial electrostatic scanning mirror with piezoresistive sensors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the idea is often hindered by the microfabrication capability to provide simultaneous driving and sensing. Therefore only few micro-scanners have demonstrated on-chip sensing capabilities [1][2][3]. As a first attempt to integrate CMOS in this work, the implementation conveniently provides piezoresistive sensing to the electromagnetically-driven scanning mirror.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] Several driving mechanisms can be used for MOEMS SGM, including electromagnetic, electrostatic, electrothermal and piezoelectric techniques. [14][15][16][17][18][19] All of them have their characteristics and can be applied to some specific applications respectively.…”
Section: Introductionmentioning
confidence: 99%